Lobbying: Buying and utilizing access - Wolfgang Mayer; Sudesh Mujumdar (Economics: The Open-Access, Open-Assessment E-Journal, 2014)
This paper develops a lobbying-by-firms model that draws on a more realistic characterization of the lobbying process; influence-seeking requires both money to 'buy access' and managerial time to 'utilize access'. This, more realistically grounded, modeling approach furnishes theoretical support for why one encounters different numbers of lobbying firms of varying sizes in different industries, without casting the (unrealistic) lifeline of the 'money-buys-policies' assumption or (unrealistically) casting out the role of money from the lobbying process. Theoretical legs are also furnished for the empirical finding of a negative and statistically significant (at the 1% level) relationship between industry concentration and 'direct lobbying' by the industry. Additional insights emerge from the model regarding how a cap on the lobbying-contributions of firms results, in fact, in an expansion of the amount of access-time purchased by some firms, and how a decline in the world price of an industry's good can generate greater inequality in access to politicians.
Keywords: H0; F16; L1; 330; Lobbying; free-rider problem; size-distribution-of-firms; world-price; labormarket-flexibility